Job insecurity and work outcomes: The role of psychological contract breach and positive psychological capital - Costa, S.; Neves, P. (Work & Stress, 2017)
Job insecurity has received growing attention from researchers because it poses serious challenges for organisations and for society as a whole. However, there are insufficient studies about the processes through which job insecurity affects outcomes as well as potential ways to reduce its negative impact. This study focuses on the relationship between job insecurity and individual level outcomes (in-role performance and organisational deviance) and examines if (a) job insecurity is positively and/or negatively related to work outcomes, (b) psychological contract breach acts as a mediator of the relationship between job insecurity and work outcomes, and (c) positive psychological capital (PsyCap) buffers the job insecurity–work outcomes relationship via psychological contract breach. With a sample of 362 employee–supervisor dyads, in which the outcome measures were collected from the supervisors, we found support for our hypotheses. Specifically, we found a moderated mediation effect, whereby PsyCap moderates the negative indirect relationship of job insecurity on outcomes through psychological contract breach.